2018
DOI: 10.1101/504704
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ComammoxNitrospiraare the dominant ammonia oxidizers in a mainstream low dissolved oxygen nitrification reactor

Abstract: Recent findings show that a subset of bacteria affiliated with Nitrospira, a genus known for its importance in nitrite oxidation for biological nutrient removal applications, are capable of complete ammonia oxidation (comammox) to nitrate. Early reports suggested that they were absent or present in low abundance in most activated sludge processes, and thus likely functionally irrelevant. Here we show the accumulation of comammox Nitrospira in a nitrifying sequencing batch reactor operated at low dissolved oxyg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
29
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 36 publications
(17 reference statements)
6
29
0
Order By: Relevance
“…These results contrast with previous studies of full-scale activated sludge WWTPs that have reported comammox Nitrospira at lower relative abundances than AOA and other AOB [7, 18-480 21], albeit for systems with ammonium concentrations and operational parameters distinct from those in the RBCs. This current study, along with other more recent studies [12,15,17,18,22], shows that comammox Nitrospira can thrive in wastewater treatment systems. Although previous analyses of the Guelph WWTP did not test for these newly discovered ammonia oxidizers [28,29], the presence of comammox Nitrospira was predicted previously from activity 485 data and an abundance of Nitrospira cells that actively assimilated labelled bicarbonate when incubated with ammonium [29].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These results contrast with previous studies of full-scale activated sludge WWTPs that have reported comammox Nitrospira at lower relative abundances than AOA and other AOB [7, 18-480 21], albeit for systems with ammonium concentrations and operational parameters distinct from those in the RBCs. This current study, along with other more recent studies [12,15,17,18,22], shows that comammox Nitrospira can thrive in wastewater treatment systems. Although previous analyses of the Guelph WWTP did not test for these newly discovered ammonia oxidizers [28,29], the presence of comammox Nitrospira was predicted previously from activity 485 data and an abundance of Nitrospira cells that actively assimilated labelled bicarbonate when incubated with ammonium [29].…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with a low ammonium niche, comammox Nitrospira have been detected in drinking water systems [7][8][9][10][11][12][13][14]. First identified from water treatment system metagenome sequences [5,6], most wastewaterassociated comammox Nitrospira belong to clade A [5, 7,12,[14][15][16][17][18], albeit with abundances generally lower than those reported for AOA and AOB [7,[18][19][20][21]. Nonetheless, amoA gene 60 abundances of comammox Nitrospira may outnumber those of AOB in activated sludge samples 4 in some WWTPs [12, 18,22], and comammox Nitrospira have been enriched in wastewater treatment reactors with low dissolved oxygen conditions, suggesting that comammox bacteria have an important role in ammonia oxidation in these reactors [15,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This predominance of canonical nitrite oxidizers in WWTP is consistent with the proposition that nitrogen-rich environments select for division of labour because it maximizes growth rates 7,31 . However, in some full-scale WWTP 19,32 and in a lab-scale low nitrification reactor 33 comammox Nitrospira have been found more abundant than canonical ammonia oxidizers, suggesting that factors beyond nitrogen fluxes influence comammox Nitrospira fitness in these systems.…”
Section: Discussionmentioning
confidence: 99%
“…Our results provide the first in-situ physiological evidence of ecologically relevant NH 4 + oxidation by comammox Nitrospira in any environment. Other reports of i n situ activity are inferred from bulk observations (ammonium removal when comammox Nitrospira are more abundant than AOBs or AOAs (20, 51)) or from comammox-specific amoA transcript analysis (52). Our former observations that Nitrospira was more abundant than Nitrosomonas and the discovery that Nitrospira harbours the complete nitrification pathway in a full-scale RGSF microbiome (8, 10, 11) is thus directly linked to the ammonia oxidizing activity of Nitrospira in this environment.…”
Section: Discussionmentioning
confidence: 99%